Company Performance Analysis with Organizational Learning as a Mediating Variable Studies on the Metal Industry in Kramat District, Tegal Regency - hutomo, prihatin tiyanto priagung; Sudirjo, Frans (Jurnal Manajemen Industri dan Logistik, 2023)
The metal industry in the Tegal city  experiences a severe shock because of  technological disruption and the Covid 19 pandemic. However,  the metal industry experiences an organizational learning process  and some of the industries are still surviving today. This study aimed  to determine the effect of Employee Engagement, Knowledge Management and Organizational Learning on the Performance of the Metal Industry in Tegal Regency, especially in Kramat District, Central Java. The population in this study was  the metal industry with a total of 121 units with a total workforce of 382 people. Samples were taken by random purposive sampling technique amounting to 78 respondents. The data analysis method used AMOS with PLS Version 3. The results of the study found that Employee Engagement, Knowledge Management, and Organizational Learning simultaneously had  a significant effect on organizational performance. Partially, Employee Engagement had  a negative and insignificant effect on Organizational Learning and Organizational Performance. Knowledge Management had  a positive and significant effect on Organizational Learning. Organizational learning has a positive effect on organizational performance. However, Organizational Learning was  not able to Mediate Employee Engagement on Organizational Performance.